A Study of Customer Satisfaction on Online Trading System Application of Securities Company in Indonesia Using Servqual - Hery Hery; Riswan Efendi Tarigan (CommIT (Communication and Information Technology) Journal, 2015)
The purpose of this study is to measure the service  quality of online trading system implemented by PT  KDB  Daewoo  Securities  Indonesia.  The study is  a part of the company  efforts to provide  the best solution  services. The study  is performed   to determine the influence of service quality  factors on the customer satisfaction by means of ServQual  method. The method takes  into account  five  independent  variables,  namely, reliability (X1 ),  responsiveness  (X2 ),  assurance  (X3 ), empathy (X4 ), and tangibility (X5 ). Meanwhile,  the cus- tomer satisfaction is considered as the dependent variable (Y ). The population of of the study  is all 67 900 online traders at the company and the sample size is 265 traders. The data are collected via questionnaires and interviews. From the study results, we conclude that the five variables have  significant  influence  on the customer  satisfaction on the online trading system application   at PT KDB Daewoo Securities Indonesia. To  improve  the customer satisfaction, the company  should prioritize the quality- related factors,  and expand  and upgrade  the existing facilities and infrastructures.